LEGAL AND ECONOMIC ASPECTS OF THE USE OF MUNICIPAL BONDS - Jakšić, Pavle; Uzelac, Ozren (Ekonomija - teorija i praksa, 2022)
By borrowing on the financial market, local self-government units in the Republic of Serbia can finance their own needs. It is up to the local self-governments to decide whether to opt for financing through credit borrowing or through the issue of municipal bonds. The subject of this paper is the analysis of the conditions and purpose for which cities, municipalities and local governments in Serbia and in the countries of the region issued municipal bonds. In this regard, the basic characteristics of the analyzed emissions are emphasized, relying on the normative framework of each country individually. The paper points out the basic specifics of municipal bonds.. The aim of this paper is to analyze the advantages and disadvantages of the issue of these bonds in relation to credit borrowing as a possible type of financing.